Meteoric water effect of diagenesis processes in deep carbonate reservoirs - Wang, Zhen; Zhang, Yiqiong; Wang, Xueke; Lin, Yaping; Jiang, Li; Zhang, Xiaozhen (Frontiers in Earth Science, 2024)
As the world’s main oil and gas resource, the deep carbonate reservoir has great exploration-development potential. However, it is difficult to make development and exploration due to its complex diagenesis processes. During the formation of carbonate reservoirs, the effect of meteoric water forms karst holes for oil and gas reservoirs, but the complex internal mechanism severely restricts the exploration and development of carbonate reservoirs. This paper takes the deep carbonate reservoirs in the Tarim Basin as the research object, studies the diagenesis processes in deep carbonate reservoirs through geological survey, analyzes the effect of meteoric water on porosity and mineral changes in carbonate reservoirs at different diagenetic stages by using laboratory test, theoretical analysis, and numerical simulation research methods. The numerical simulation method is used to simulate the porosity changes and mineral evolution of reservoirs in different diagenetic stages, and the conclusion is drawn that meteoric water has an impact on reservoir minerals and porosity. The results show that the carbonate reservoirs in the Tarim Basin have high porosity and good permeability, and the reservoirs have experienced deposition, compaction, dissolution, and hydrothermal stages, and have experienced meteoric water effects for a long time, resulting in rock dissolution, regenerative precipitation and chemical reaction; Quartz and feldspar minerals are the most in the sample through laboratory tests, the content of quartz decreased first, then increased and decreased, and the content of chlorite and mica changed little during the whole diagenesis processes. With the injection of organic acid, the porosity of the reservoir increases, with the continuous increase of temperature and pressure, the porosity decreases. After the second injection of organic acid, the porosity increases continuously, and finally, the porosity decreases. TOUGHREACT is used to simulate the static reaction of water and rock, simulating six diagenetic stages. With the injection of organic acid, the porosity increases continuously and then reaches equilibrium. The sudden increase in temperature and pressure leads to an increase in porosity, and the porosity of the reservoir changes little during the second injection of organic acid, and the porosity decreases in the final stage. The research results provide theoretical data support for guiding oil and gas exploration in deep carbonate reservoirs.